Gender differences in climate change perception and adaptation strategies: A case study on three provinces in Vietnam’s Mekong River Delta - McKinley J; Adaro, C.; Pede, Valerien O.; Setiyono T; Tran CT; Do LH; Nguyen TK; Quicho E; Sheinkman, Michael; Wassmann, Reiner (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
This brief summarizes the findings of a project output for the Policy Information and Response Platform on Climate Change and Rice in ASEAN and its Member Countries (PIRCCA), being implemented by the International Rice Research Institute (IRRI). The report focuses on the results of the survey conducted in the first half of 2015 on climate change perception and adaptation strategies of male and female farmers in three selected provinces across the Mekong River Delta (MRD) region in Vietnam: An Giang, Bac Lieu, and Tra Vihn. The survey gathered information on current climate change perceptions and adaptation strategies and gaps between the identified male and female respondents.